Penanggulangan Tindak Pidana Penyalahgunaan Data Pribadi Dalam Sistem Elektronik di Indonesia: Kajian Perbandingan Hukum Inggris dan Hukum Indonesia - Rahmadany, Annisa Zahra; Erdiansyah, Erdiansyah; T. Arif Hidayat (CV. ULIL ALBAB CORP, 2025)
Criminal acts involving the misuse of personal data encompass a series of illegal actions, including the collection, processing, or use of personal information without the consent or authorization of the individual concerned. In today’s digital context, where personal information is highly valuable, such actions can occur in various ways, including data theft through hacking, wiretapping, or social engineering techniques. This research is a normative legal study. A normative legal study is conducted by examining literature or secondary data consisting of primary, secondary, and tertiary legal materials. The findings of this study indicate that the regulation of criminal acts related to the misuse of personal data in Indonesia and the United Kingdom shares the same objective: to protect individuals’ rights concerning personal data and to ensure public trust in data management. However, there are significant differences in terms of regulatory clarity, sanctions, supervision, and transparency.